Optimization of surgical treatment of diabetic foot syndrome in Saratov region - Osintsev E.Yu.; Melsitov V.A. (Саратовский научно-медицинский журнал, 2012)
The research goal is to estimate the results of multidisciplinary approach to treatment of diabetic foot syndrome in the conditions of specialized hospital centre. Materials and methods: The clinical part of work is based on the study of surgical assistance range, recurrence of infectious complications of diabetes mellitus and mortality rate in 226 diabetic foot syndrome patients. Optimum results of treatment have been received in a group of patients with neuropathic forms of lower extremities damage. Conclusion: Use of multidisciplinary approach to the treatment of patients with complications of diabetes mellitus has improved survival rate (x2=12,1; p=0,002) and quality of life of patients with diabetic foot syndrome in Saratov region